PENGARUH MEDIA ACTIVITY BEL TERHADAP SIKAP TANGGUNG JAWAB ANAK USIA 5-6 TAHUN - Rosdiana Sibarani; Enda Puspitasari; Defni Satria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine the effect of media activity bells on the responsible attitude of children aged 5-6 years. This type of research is experimental research, with a one group pretest posttest pre-experimental design. The population in this study were all children A ALFA OMEGA KIDS PAUD, this research method was carried out by observation and a sample of 15 children. Test the significance of this difference with the t statistic obtained tcount = 22.736 with sig = 0.00 <0.05. Because the Sig value <0.05 means significant. So there is a significant difference in changes in the attitude of responsibility in children between before and after using the Activity Bell media. After treatment has a greater effect than before treatment. The results of this study indicate that the use of Activity Bell media for responsible attitudes is 77.50%.Key Words: Responsibilities, Activity bell